Redefining the Distributional Boundaries and Phylogenetic Relationships for Ctenomids From Central Argentina - Carnovale, Cecilia Soledad; Fernández, Gabriela Paula; Merino, Mariano Lisandro; Mora, Matías Sebastián (Frontiers in Genetics, 2021)
With about 68 recognized living species, subterranean rodents of the genus Ctenomys are found in a multiplicity of habitats, from the dunes of the Atlantic coast to the Andes Mountains, including environments ranging from humid steppes of Pampas to the dry deserts of Chaco region. However, this genus needs an exhaustive reevaluation of its systematic and phylogenetic relationships regarding the different groups that compose it. This knowledge is essential to propose biodiversity conservation strategies both at species level and at higher hierarchical levels. In order to clarify the taxonomy and the recent evolutionary history from populations of Ctenomys in the Pampas region, Argentina, phylogenetic relationships among them were evaluated using mitochondrial DNA sequences: gene encoding cytochrome b protein (1,140 bp) and the non-coding D-loop region (434 bp). To infer the divergence times inside the Ctenomys clade, a Bayesian calibrate tree using fossil remains data from different families within Caviomorpha was performed at first. Secondly, that calibration data was used as priors in a new Bayesian phylogenetic inference within the genus Ctenomys. This phylogenetic tree emphasized on species currently distributed on the Pampas region, more precisely considering both the talarum and mendocinus groups. Bayesian inferences (BI) were integrated with the results of a Maximum Likelihood approach (ML). Based on these results, the distributional limits of the mendocinus and talarum groups appear to be related to the physiognomy of the Pampas region soils. On the other hand, the validity of C. pundti complex as a differentiated species of C. talarum is debated. According to previous evidence from morphological and chromosomal studies, these results show a very low divergence between those species that originally were classified within the talarum group. Mitochondrial DNA sequences from populations associated with these putative species have not recovered as reciprocal monophyletic groups in the phylogenetic analyses. In conclusion, C. talarum and C. pundti complex might be considered as the same biological species, or lineages going through a recent or incipient differentiation process. The results obtained in this study have important implications for conservation policies and practices, since both species are currently categorized as Vulnerable and Endangered, respectively.